Electronic structure formed by Y2O3-doping in lithium position assists improvement of charging-voltage for high-nickel cathodes - Shijie Wang; Kang Liang; Hongshun Zhao; Min Wu; Junfeng He; Peng Wei; Zhengping Ding; Jianbin Li; Xiaobing Huang; Yurong Ren (Nature Communications)
Abstract High-capacity power battery can be attained through the elevation of the cut-off voltage for LiNi0.83Co0.12Mn0.05O2 high-nickel material. Nevertheless, unstable lattice oxygen would be released during the lithium deep extraction. To solve the above issues, the electronic structure is reconstructed by substituting Li+ ions with Y3+ ions. The dopant within the Li layer could transfer electrons to the adjacent lattice oxygen. Subsequently, the accumulated electrons in the oxygen site are transferred to nickel of highly valence state under the action of the reduction coupling mechanism. The modified strategy suppresses the generation of oxygen defects by regulating the local electronic structure, but more importantly, it reduces the concentration of highly reactive Ni4+ species during the charging state, thus avoiding the evolution of an unexpected phase transition. Strengthening the coupling strength between the lithium layers and transition metal layers finally realizes the fast-charging performance improvement and the cycling stability enhancement under high voltage.